Analytical determinations of luteolin - Tesio, Alvaro Yamil (2021)
Plants, through the photosynthesis process, produce the substances necessary for all the life cycles of nature, which are called "primary metabolites." Moreover, there are some plants that synthesize, in addition to these, other substances with more specific functions, which are known as "secondary metabolites." It is inside this group that flavonoids are located, whose main function is to protect organisms from damage caused by different oxidizing agents. Luteolin (3,4,5,7-tetrahydroxy-flavone) belongs to the sub-class of flavonoids known as flavones and is one of 10,000 flavonoids currently known, being one of the most bio-active flavonoids. Its various beneficial properties for health, together with the increasing reduction in the use of synthetic antioxidants, make the study of luteolin a very active field. Within this, the quantification of this molecule has become a subject of very special interest given that it is transversal to all fields. In this review article, we aim to give the reader a broad and deep vision of this topic, focusing on the events reported in the last 5 years and covering all possible techniques related to analytical determinations. We will discuss in terms of advantages and disadvantages between techniques, selectivity, sensitivity, costs, time consumption, and reagents as well as in the complexity of operations.